Technetium Tc 99m Dimercaptosuccinic Acid Renal Scintigraphy in Children With Acute Pyelonephritis: Correlation With Other Imaging Tests (Iranian Journal of Kidney Diseases, 2010)
Introduction. Urinary tract infection is the most common serious bacterial infection in children. The aim of this study was to compare the value of different laboratory and imaging techniques in detecting renal involvement in acute pyelonephritis.Materials and Methods. In a cross-sectional study of patients 1 month to 14 years of age diagnosed with urinary tract infection were examined with systemic inflammatory markers, renal ultrasonography, voiding cystourethrography (VCUG), and technetium Tc 99m dimercaptosuccinic acid (99mTc-DMSA) renal scintigraphy. A total of 1467 pediatric patients were eligible for treatment of pyelonephritis. Evaluations included a complete blood count, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), urinalysis, urine culture, and measurement of serum blood urea nitrogen and creatinine levels.Results. The results of 99mTc-DMSA scans were normal in 20.2%, mild decreased cortical uptake in 45.0%, moderate decreased cortical uptake in 12.3%, severe decreased cortical uptake in 12.0%, and decreased cortical function plus irregularity or scar formation in 10.5%. Voiding cystourethrography showed vesicoureteral reflux in 25.9%. The sensitivity of 99mTc-DMSA for prediction of vesicoureteral reflux was 84.1% with a negative predictive value of 80.6%. Significant differences were found in the level of blood leukocyte count (P = .03), urine leukocyte count (P = .003), ESR (P = .008), and age (P = .04) between patients with normal and abnormal 99mTc-DMSA scan results.Conclusions. We found that in patient with clinical signs of pyelonephritis, 99mTc-DMSA renal scintigraphy can detect pyelonephritis more accurately than the other inflammatory and imaging tests.